1-h Postprandial glucose level is related to the serum anti-Müllerian hormone level in women with polycystic ovary syndrome. (3rd October 2015) - Chun, Sungwook
Abstract: The aim of this study was to evaluate the relationship between the serum anti-Müllerian hormone (AMH) level and parameters related to insulin resistance in Korean women with polycystic ovary syndrome (PCOS). A total of 95 Korean women aged 18–33 years who were newly diagnosed with PCOS according to the Rotterdam Consensus at a university hospital were included in this study. Blood samples were collected from all participants during the early follicular phase using tubes without anticoagulants after an overnight fasting to determine the serum AMH level and other biochemical parameters, and then a standard 2-h 75-g oral glucose tolerance test (OGTT) was performed for all participants. All patients with PCOS were divided into two groups based on the serum AMH level: group 1 (AMH < 10.0 ng/ml) and group 2 (AMH ≥ 10.0 ng/ml). The clinical variables were not significantly different between the two groups. The mean postprandial glucose level at 1 h (PPG1) in group 1 (111.70 ± 4.9 mg/dl) was significantly lower than that in group 2 (136.76 ± 9.86 mg/dl). No significant differences between the two groups were found in the other insulin resistance-related parameters. In conclusion, the serum AMH level may be related to PPG1 in women with PCOS.